2016
DOI: 10.1038/srep30286
|View full text |Cite
|
Sign up to set email alerts
|

Detecting early signs of the 2007–2008 crisis in the world trade

Abstract: Since 2007, several contributions have tried to identify early-warning signals of the financial crisis. However, the vast majority of analyses has focused on financial systems and little theoretical work has been done on the economic counterpart. In the present paper we fill this gap and employ the theoretical tools of network theory to shed light on the response of world trade to the financial crisis of 2007 and the economic recession of 2008–2009. We have explored the evolution of the bipartite World Trade W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 38 publications
3
90
0
Order By: Relevance
“…of the similarity of export baskets, before the financial crisis [79]. This development Note that the last results do not imply any causal relation, as discussed in [79]. However, the dramatic evolution of the closed motifs anticipated the crisis.…”
Section: Motif Validation In Tradementioning
confidence: 73%
See 2 more Smart Citations
“…of the similarity of export baskets, before the financial crisis [79]. This development Note that the last results do not imply any causal relation, as discussed in [79]. However, the dramatic evolution of the closed motifs anticipated the crisis.…”
Section: Motif Validation In Tradementioning
confidence: 73%
“…Although purely data-based analyses provide valuable insight into the mechanisms of networks, recent results have shown that such structures contain more information than is apparent at first sight. In particular, several techniques have been designed based on statistical physics and information theory, which provide the possibility to filter statistically relevant signals from the network that otherwise remain hidden when the data is take at face value [80,79,88,49,85].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…with now allFc andPp set to be equal to their mean field valuef andp, respectively. By setting δ = 0, we findp = 1/(1 − C P ) ≈ 1 + C P andf = P − C. Indeed, an approximate expression for the fixed point of Equation (6) in the regime δ 1 and C P can be derived also beyond the mean field approximation. To this end, we set again δ = 0 and consider the corresponding fixed point equation associated to Equation (6), i.e.…”
Section: Analytic Approximate Solutionmentioning
confidence: 80%
“…A particularly interesting issue concerns the detection of early-warning signals of upcoming critical events. As shown in [127], this can be done by computing z X for each temporal snapshot of the considered system 16 and, then, plotting z X (t) versus t. As far as the discrepancy between observed and expected values evolves "smoothly" from out-of-equilibrium to equilibrium states (or vice-versa), early-warning signals can be possibly detected [128,129], An important aspect of a network to be tested for statistical significance is, without doubts, its mesoscale organization into modules or communities. An approach similar to what presented in the previous subsection works as follows [130].…”
Section: What May and What May Not Be Reconstructedmentioning
confidence: 99%